OPINION SURVEY OF THE CARDIOLOGISTS IN BULGARIA REGARDING THERAPY WITH ACETYLSALICYLIC ACID, CLOPIDOGREL AND ACENOCOUMAROL IN PATIENTS UNDERGOING DENTAL EXTRACTIONS - Atanaska Dinkova; Dimitar Atanasov; Lyudmila Vladimirova-Kitova (Peytchinski Publishing, 2017)
Purpose: Cardiovascular diseases are the leading cause of mortality and disability worldwide. Major role in the treatment and prophylaxis of these diseases and their complications has antiplatelet and anticoagulation therapy. Routine practice in the past was an interruption of antiplatelet and anticoagulant medication before dental extraction. Today most authors and dental associations recommend maintaining therapeutic levels of antithrombotic drugs in single or multiple teeth extractions due to the fact that the risk of serious embolic complications outweighs the risk of bleeding. The aim f the present study is to determine the opinion and approach of cardiologists in Bulgaria regarding therapy with Aspirin, Clopidogrel and Acenocoumarol in patients undergoing dental extractions. Material and Method: 222 cardiologists were interviewed about their approach in terms of antithrombotic therapy with acetylsalicylic acid (Aspirin), Clopidogrel (Plavix, Trombex) and Acenocoumarol (Sintrom) in patients undergoing dental extractions. Results: There is no consensus and an established protocol the cessation of enrolled medications and how long before dental extraction. Conclusion: There is no approved protocol regarding administration of acetylsalicylic acid (Aspirin) Clopidogrel (Plavix, Trombex) and Acenocoumarol (Sintrom) in patients undergoing teeth extraction. A large number of thromboembolic complications due to interruption of the therapy has been reported